2007
DOI: 10.1038/emm.2007.43
|View full text |Cite
|
Sign up to set email alerts
|

Swim training improves leptin receptor deficiency-induced obesity and lipid disorder by activating uncoupling proteins

Abstract: Leptin receptor deficiency causes morbid obesity and hyperlipidemia in mice. Since physical exercise enhances energy expenditure, it is an important part of successful weight-control regimens. We investigated the mechanism by which swim training regulates leptin receptor deficiency-induced obesity and lipid disorder in a mouse model of obesity (obese db/db mouse). Swim training for 6 weeks significantly decreased body weight gain and adipose tissue mass in both sexes of obese and lean mice, compared to their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…Thaxton et al (2006) found no influence on GLU, CHOL, and TRI on a stressing situation in overcrowded male broilers, whereas CS showed greater values compared with control. Our findings appear logical, because body fat content and concentration of TRI are linked (Oh et al, 2007). Indeed, a comparable TRI concentration between treatments reaches conclusions similar to those by Madec et al (2006), who observed no statistical differences in body fat between MHUSA and control.…”
Section: Discussionsupporting
confidence: 87%
“…Thaxton et al (2006) found no influence on GLU, CHOL, and TRI on a stressing situation in overcrowded male broilers, whereas CS showed greater values compared with control. Our findings appear logical, because body fat content and concentration of TRI are linked (Oh et al, 2007). Indeed, a comparable TRI concentration between treatments reaches conclusions similar to those by Madec et al (2006), who observed no statistical differences in body fat between MHUSA and control.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, lack of leptin receptors renders skeletal muscles more oxidative and fatigue resistant which is similar to skeletal muscle from aged mice [43]. Obviously, skeletal muscles of genetically obese mice did not respond to changes in body weight or activity [44], even though swim training improves leptin receptor deficiency-induced obesity by leptin-independent mechanism [45]. Physiologically, distinct leptin concentrations are evident in sexual dimorphism [46], whereas in pathology higher blood plasma leptin was found in cancer cachexia [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…UCP-1 has recently attracted attention as a target for suppressing obesity. CSNs and exercise have been reported to increase UCP-1 levels in interscapular BAT (31,37,38). Furthermore, exercise has been reported to induce browning in subcutaneous WAT (5).…”
Section: Discussionmentioning
confidence: 99%